Identifikasi Formalin Pada Ikan Segar di Pelabuhan Pendaratan Ikan Idi Rayeuk Kabupaten Aceh Timur - Rosa Mardiana; Lidyawati Lidyawati; Muhammad Zulfikri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Indonesia is the second largest country after China in terms of capture fisheries production. Capture fisheries production in Indonesia in 2016 reached 6.83 million tons with a value of Rp. 125.3 trillion. The abundant fishery potential causes the fish preservation process at the fishermen level to be constrained. The limited number of preservatives that are safe for food makes formaldehyde an alternative preservative. The use of formaldehyde in food can cause poisoning to the human body.In the formaldehyde test conducted by the Integrated Supervision Team of the Aceh Marine and Fisheries Service (DKP) in 2017 it was found that the practice of using formalin as a fish preservative was still used by some fishermen and fish traders in Indonesia. Aceh. This research was conducted to determine the sustainability of the practice of using formaldehyde by fishermen and traders by identifying the formalin content in tuna and mackerel in Idi Rayeuk Fish Landing Port, East Aceh Regency. The samples used in this study were 3 tuna and 3 mackerel fish taken randomly at the Idi Rayeuk Fish Landing Site, East Aceh. The results showed that all samples tested showed negative results or the fish did not contain formaldehyde. This shows that the public and fishermen's awareness of the dangers of formaldehyde is very good.